Redesigning of Signals and Systems Course to Emphasize Problem/Project Based and Experiential Learning - Reddy, Poli Lokeshwara; Singh, D Narendar (Journal of Engineering Education Transformations, 2025)
The prime trait of engineering education which persistently challenges to tide over classroom and real-world scenario is its cornerstone on fortifying future technocrats to design and implement various systems of engineering. This paper introduces the experimental study of signals and systems course in an under graduate(UG) program by using problem/project-based learning at Anurag University, which makes the learners to acquire iterative and collaborative skills to solve real world complex problems in practical approach subjects. The major objective of this framework is to enrich the conventional course of study with value creation, responsive content, practices and larks providing a competitive scope to learners. The specified approach do enhances the learning spirit among the learners by doing the things which intern results in experiential learning. The problem/project based learning enactment frame and constructive alignment of course outcomes, teaching/learning methods and assessment are specified in the paper.